Edukasi Gizi Melalui Penanaman Kangkung (Ipomoea Aquatica) Organik di Perkarangan Rumah - Gusnovia Windri Yani; Sukamarriko Andrikasmi; Awwalia Puti Haura; Boges Pedrochi; Yafinda Deansya; Rona Kartika; Hesti Lestari; Rahama Septia Dariska; Jarga Juara Uli Parsaroan; Herlina Audya; Indriani Hadisti; Wan Boyke Pande Sinaga (Unri Conference Series: Community Engagement, 2025)
The consumption of fresh, nutrient-rich vegetables in Merempan Hilir Village, Mempura Subdistrict, Siak Regency remains low, resulting in suboptimal community nutritional status. One solution to improve access to and consumption of healthy vegetables while supporting household food security is the cultivation of organic water spinach (Ipomoea aquatica) in home gardens. Organic water spinach is environmentally friendly and rich in essential nutrients such as vitamin A, vitamin C, iron, and dietary fiber. This program applied a nutrition education approach delivered directly to housewives, including counseling on the importance of balanced nutrition and training in organic water spinach cultivation techniques. Nutrition education aims to change attitudes and behaviors by providing knowledge and skills so participants can independently adopt healthy eating habits. The results showed that the community began cultivating organic water spinach in home gardens and consuming it regularly, thereby improving healthy vegetable consumption behavior and contributing to long-term household food security and family health.